Pentingnya Kepemimpinan dan Kemampuan Manajerial untuk Peningkatan Mutu Lembaga Pendidikan - Putu Sanjaya (UHN IGB Sugriwa Denpasar, 2016)
An institution or organization can never be separated from management and leadership style. a leader whose leadership style is certainly different one with the other leaders even though it was likely to be no similarity between the leadership styles are applied in addition to the managerial skills of a leader will determine the course of an institution or organization.